IMMUNOLOGY OF IL-12: AN UPDATE ON FUNCTIONAL ACTIVITIES AND IMPLICATIONS FOR DISEASE - Ullrich, Karen; Schulze, Lisa; Paap, Eva-Maria; Müller, Tanja; Neurath, Markus; Zundler, Sebastian (Excli Journal, 2020)
As its first identified member, Interleukin-12 (IL-12) named a whole family of cytokines. In response to pathogens, the heterodimeric protein, consisting of the two subunits p35 and p40, is secreted by phagocytic cells. Binding of IL-12 to the IL-12 receptor (IL-12R) on T and natural killer (NK) cells leads to signaling via signal transducer and activator of transcription 4 (STAT4) and subsequent interferon gamma (IFN-gamma) production and secretion. Signaling downstream of IFN-gamma includes activation of T-box transcription factor TBX21 (Tbet) and induces pro-inflammatory functions of T helper 1 (T(H)1) cells, thereby linking innate and adaptive immune responses. Initial views on the role of IL-12 and clinical efforts to translate them into therapeutic approaches had to be re-interpreted following the discovery of other members of the IL-12 family, such as IL-23, sharing a subunit with IL-12. However, the importance of IL-12 with regard to immune processes in the context of infection and (auto-) inflammation is still beyond doubt. In this review, we will provide an update on functional activities of IL-12 and their implications for disease. We will begin with a summary on structure and function of the cytokine itself as well as its receptor and outline the signal transduction and the transcriptional regulation of IL-12 secretion. In the second part of the review, we will depict the involvement of IL-12 in immune-mediated diseases and relevant experimental disease models, while also providing an outlook on potential translational approaches.
CRIS-Team WoS Importer:2021-01-15